Cost-effectiveness of susceptibility-guided therapy under varying rates of clarithromycin resistance - Shihan Xu; Xianzhu Zhou; Yiqi Du (The Lancet Regional Health. Western Pacific)
Background: With resistance of Helicobacter polyri to antibiotics reaching alarming levels worldwide, the Maastricht VI/Florence consensus report recommended that susceptibility tests are routinely performed to improve cure rates, even before prescribing first-line treatment. However, the routine use of susceptibility-guided test in clinical practice remains to be established owing to economical and practical issues. We conducted a decision analysis to compare the cost-effectiveness of susceptibility-guided versus empirical therapy for treatment-naïve H. pylori patients, considering the changing rates of clarithromycin resistance. Methods: A decision analysis model is developed to estimate the costs, health outcomes, and cost-effectiveness of our research protocol, using TreeAge Pro (Healthcare Version) 2022 (TreeAge Software). The protocol is mainly based on the 2022 Chinese guideline on Hp eradication treatment and expert opinion. We hypothesized that H. pylori-infected, treatment-naive patients would undergo empirical or susceptibility-guided first-line and second-line treatment. Patients who failed second-line treatment were considered to have failed eradication. In the empirical treatment (EMT) group, clarithromycin quadruple therapy and Levofloxacin quadruple therapy are used as the first-line and second-line regimens, respectively. In the susceptibility-guided therapy (SGT) group, patients with clarithromycin resistance are initially treated with high-dose dual therapy, while those sensitive to clarithromycin receive clarithromycin quadruple therapy. Furazolidone quadruple therapy is employed as the second-line regimen in SGT group. Model parameters are derived from previous literature and China Medical Insurance. Findings: In the base case analysis (clarithromycin resistant rate =37%), it takes $3757.01 to additionally cure 1 Hp-infected patient using SGT compared to EMT, and the ICER tended to decrease sharply following the increase of clarithromycin resistance rate. Besides, the average cost of EMT tended to increase subsequent to the increase of clarithromycin resistance rate, in contrast to SGT. However, the cost of SGT treatment consistently exceeds that of EMT by more than $70. Following the implementation of second-line therapy, the eradication rate in the SGT group improves by no more than 5% compared to the EMT group. Interpretation: This study showed that SGT is more effective but requires additional costs, thus being inferior to the EMT group in terms of cost-effectiveness. This may be because of the following points: First, the addition of bismuth ensures that the clarithromycin quadruple therapy maintains a high eradication rate even in patients with clarithromycin resistance. Second, after the administration of second-line therapy, the EMT group achieves a high eradication rate of over 90%, even if clarithromycin resistance rate reaches 100%, diminishing the advantage of the SGT group. Third, the high cost of susceptibility testing significantly increases the expense of SGT compared to EMT. This study is the first to explore the health economics benefits of SGT under varying rates of clarithromycin resistance. SGT is at a cost disadvantage, but it remains superior in efficacy. With advancements in susceptibility testing technology and reduced costs, the expense of SGT may further decrease, enhancing its value for routine application, particularly in the context of high antibiotic resistance in Helicobacter pylori, which poses a significant threat to human health.